Sistem Identifikasi Pencemaran Air Sungai Berbasis Internet Of Things - Eli Widyawati, Reza; Audytra, Hastie; Aristia Sa'ida, Ita (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2024)
Rivers are open-water ecosystems that are vulnerable to pollution or damage. Pollution that occurs in rivers is usually caused by environmental conditions and human activity that settles around the river. Water ecosystems consist of interrelated biotic and abiotic components; when both components are interrupted, changes in the ecosystem become unbalanced. Water pollution can be caused either intentionally or accidentally, but the main factor in the occurrence of water contamination that is often found is the result of human activity. Technology in this era is evolving very fast. Therefore, there are many prototypes that can support the development of such technologies, such as node-MCU and the Internet of Things (IOT). NodeMCU is a microcontroller equipped with the WiFi module ESP8266. NodeMCU also has a relatively cheaper price.The test results on this system were obtained by conducting a black box test and a validity test on an IOT-based river water pollution identification system using a pH sensor and a turbidity sensor. The results of testing the application of fuzzy sugeno produce a value of 100% from the compatibility of the 3 tests, namely testing on the system, matlab and manual calculations.He suggested that this system could make it easier to know the quality of contaminated or uncontaminated river water.